Unveiling the links between physical activity, self-identity, social anxiety, and emotional eating among overweight and obese young adults - Wang, Huilin; He, Xianyi; Tang, Yiwei; Tang, Jiaxin; Yang, Jingyu (Frontiers in Psychology, 2024)
Introduction Emotional eating not only contributes to physical obesity but also leads to the experience of guilt and shame, exacerbating emotional problems. Increasing physical activity, adopting a balanced diet, and seeking psychological support help improve emotional eating issues in overweight or obese young adults, enhancing overall mental and physical well-being. Methods This study investigates the correlation between physical activity, self-identity, social anxiety, and emotional eating among 373 overweight and obese college students aged 18–26 in central China. By utilizing AMOS v.26, a structural equation model was constructed to examine the hypotheses. Results The findings reveal that physical activity significantly influences self-identity and social anxiety, which, in turn, significantly impact emotional eating. Moreover, self-identity and social anxiety serve as mediators in the relationship between physical activity and emotional eating. These results emphasize the role of physical activity in mitigating emotional eating among young individuals struggling with overweight and obesity. Discussion Consequently, the government and relevant agencies are urged to address the issue of obesity among young adults and provide support for their engagement in physical activity.